Moringa oleifera leaf production as affected by different row to row and plant to plant spacing - Abdul Fatah Soomro; Abdul Ahad Kolachi; Nisar Ahmad Soomro; Muhammad Mansoor; Sindhu Abbasi; and Ijaz Ahmad (Indus Journal of Bioscience Research, 2024)
A field experiment was conducted at the Institute of Plant Introduction (IPI) Farm, Saleh Muhammad village, Malir, Southern Zone Agriculture Research Center, Karachi (24°25.11'N, 67°14.89'E), Pakistan, during 2018-2019 using a randomized complete block design with two factors: plant spacing (20 x 20 cm, 40 x 40 cm, and 60 x 60 cm) and three successive cuttings. The objective was to determine the optimum plant population for maximum leaf production. Results showed significant differences in M. oleifera leaf yield based on spacing and cutting time. For spacing treatments, the highest green leaf yield per acre was recorded at 40 x 40 cm spacing with 4292.2 kg, followed by 60 x 60 cm and 20 x 20 cm spacing, yielding 2821.1 kg and 2492.7 kg respectively. Similarly, the highest dry leaf yield per acre was also at 40 x 40 cm spacing with 583.67 kg, compared to 436.78 kg and 385.44 kg for 60 x 60 cm and 20 x 20 cm spacing respectively. Among the cuttings, the third cutting resulted in the highest green and dry yields per acre at 6189.8 kg and 874.11 kg respectively, followed by the second cutting (2311.9 kg and 369.11 kg) and the first cutting (1104.3 kg and 162.67 kg). These results indicate that an intermediate spacing of 40 x 40 cm optimizes leaf yield per acre, while subsequent cuttings enhance overall production. This study provides valuable insights for optimizing Moringa leaf production in similar agro-ecological conditions